The minimal-span channel for rough-wall turbulent flows - MacDonald M.; Chung D.; Hutchins N.; Chan L.; Ooi A.; Garci-Mayoral R. (Cambridge University Press, 2023)
Boundary layers; Pressure gradient; Quay walls; Reynolds number; Shear stress; Turbulence; Turbulent flow; Wall flow; Computational time; Hydraulic behaviour; Improving performance; Pressure-gradient parameters; Statistical uncertainty; Stream-wise velocities; Turbulence simulation; Turbulent boundary layers; Shear flow; channel flow; flow modeling; pressure gradient; Reynolds number; shear stress; surface roughness; turbulence; turbulent boundary layer; turbulent flow